Clinical characteristics of early- and late-onset gout: A cross-sectional observational study from a Chinese gout clinic. Issue 47 (November 2016) - Zhang, Bingqing; Fang, Weigang; Zeng, Xuejun; Zhang, Yun; Ma, Ya; Sheng, Feng; Zhang, Xinlei
Abstract : Abstract: A retrospective cross-sectional study using data from an outpatient clinic in China was conducted to investigate the clinical features of early-onset gout patients. All patients diagnosed with gout were asked about clinical characteristics of their gout and comorbid diseases. Patients presenting with acute flares were asked about common triggers before the flare. "Early-onset" gout was defined as onset of gout before 40 years and "late-onset" as onset ≥40 years. Major joint involvement, flare frequency before presentation, the cumulative number of involved joints, proportions of tophi complications at presentation, flare triggers, as well as any metabolic, cardiovascular, cerebrovascular, and renal comorbidities, were compared between the 2 groups. A total of 778 gout patients were enrolled in this study, including 449 (57.7%) in the early-onset group and 329 (42.3%) in the late-onset group. Compared with the late-onset gout patients, the early-onset gout patients had a higher proportion of ankle/mid-foot involvement (62.8% vs 48.2%, P  < 0.001), more frequent flares before presentation (11.2 ± 1.17 vs 6.97 ± 1.03 times per year, P  = 0.01), higher cumulative number of involved joints (5.2 ± 0.26 vs 3.8 ± 0.26, P  < 0.001), and more likely to have alcohol consumption as a flare trigger (65.2% vs 53.9%, P  = 0.03); whereas early-onset gout patients had fewer metabolic, cardiovascular, cerebrovascular, or renal complications. Early- and late-onset gout patients had different clinical features. Early-onset seems to be influenced more by lifestyle, while late-onset patients have more complications because of comorbidities. Abstract : Supplemental Digital Content is available in the text